"Nosque Filio in haereditatem a Deo patre donamur (De Trinitate 4,37)": El hombre como herencia dada a Cristo por Dios Padre: una reflexión en torno al concepto paulino de κληρονομία en la obra de Hilario de Poitiers - Alba López, Almudena (Scripta theologica, 2022)
Hilary of Poitiers reflects Paul’s thoughts on the notion of "inheritance" by exploring and incorporating new aspects and taking it one step further by understanding that mankind has been given to Christ as an inheritance by God the Father. We will approach the influence of Paul's thought on inheritance in Hilary of Poitiers by examining his reflections on the main passages in which Paul of Tarsus specifically covers the subject in question and its connection to other related aspects, such as the notion of "promise", as well as those in which the Abrahamic and Davidic covenants play an essential role.